Dampak Sosial Ekonomi Bencana Banjir dan Pemetaannya Berbasis Sistem Informasi Geografis (SIG) - Ratnaningsih, Tri Kurniawati; Rahayu, Heffi Christya; Lestari, Etty Puji; Sultan, Sultan; Fathoni, Ahmad (Jurnal Samudra Ekonomi dan Bisnis, 2023)
The purpose of this study was to determine the distribution of flood locations in the Rokan Hulu regional administrative area and to determine the socio-economic impact of flooded households by modeling the distribution of flood locations based on Geographic Information Systems (GIS). The population is residential residents of Rokan Hulu Regency and floodplain sampling points located in the floodplains. The possibility of a flood disaster in Rokan Hulu Regency is very vulnerable and is divided into 16 districts. The research data was evaluated using point analysis method. There are two types of spatial mapping used, namely spatial mapping and spatial overlay. Spatial mapping is a description of conditions on a map, while spatial overlay is an analysis of several maps to create a new map. This mapping produces a flood hazard map, as well as a combination of point analysis and coverage analysis.